Estetrol Modulates Endothelial Nitric Oxide Synthesis in Human Endothelial Cells - Montt-Guevara, Maria Magdalena; Giretti, Maria Silvia; Russo, Eleonora; Giannini, Andrea; Mannella, Paolo; Genazzani, Andrea Riccardo; Genazzani, Alessandro David; Simoncini, Tommaso (Frontiers in Endocrinology, 2015)
Estetrol (E4) is a natural human estrogen that is present at high concentrations during pregnancy. E4 has been reported to act as an endogenous estrogen receptor modulator, exerting estrogenic actions on the endometrium or the central nervous system but presenting antagonistic effects on the breast. Due to these characteristics, E4 is currently being developed for a number of clinical applications, including contraception and menopausal hormone therapy. Endothelial nitric oxide (NO) is a key player for vascular function and disease during pregnancy and throughout ageing in women. Endothelial NO is an established target of estrogens that enhance its formation in human endothelial cells. We here addressed the effects of E4 on the activity and expression of the endothelial nitric oxide synthase (eNOS) in cultured human umbilical vein endothelial cells (HUVEC). E4 stimulated the activation of eNOS and NO secretion in HUVEC. E4 was significantly less effective compared to E2 and a peculiar concentration-dependent effect was found, with higher amounts of E4 being less effective than lower concentrations. When E2 was combined with E4, an interesting pattern was noted. E4 antagonized NO synthesis induced by pregnancy-like E2 concentrations. However, E4 did not impede the modest induction of NO synthesis associated with postmenopausal-like E2 levels. These results support the hypothesis that E4 may be a regulator of NO synthesis in endothelial cells and raise questions on its peculiar signaling in this context. Our results may be useful to interpret the role of E4 during human pregnancy and possibly to help develop this interesting steroid for clinical use.